2018
DOI: 10.1016/j.jped.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with parental underestimation of child's weight status

Abstract: Since awareness of weight problems is essential for prevention and treatment, clinical practitioners should help parents at high risk of misperception to correctly evaluate their child's weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
1
14
0
10
Order By: Relevance
“…Because child weight data were not collected, there is also a possibility that children were not overweight or obese and the mothers would not be concerned about child weight. Further, it is well documented that parents tend to underestimate their child's own weight status, with parents of children that are overweight or obese commonly perceiving their child as normal weight ( 40 ). In older children it has been shown that parents who have multiple children have a lower chance of underestimation of child weight ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because child weight data were not collected, there is also a possibility that children were not overweight or obese and the mothers would not be concerned about child weight. Further, it is well documented that parents tend to underestimate their child's own weight status, with parents of children that are overweight or obese commonly perceiving their child as normal weight ( 40 ). In older children it has been shown that parents who have multiple children have a lower chance of underestimation of child weight ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 Although Robinson 47 found that perceiving a child is 'fat', still tends to correlate with their future weight, Etelson et al, 48 suggested pediatricians should provide weight loss advice to parents, and focus on both the assessment of the parent's perceptions, as well as their understandings of this problem. Warkentin et al, 29 propose that since awareness of weight problems is essential for prevention and treatment, clinical practitioners can help parents at high risk of misperception to correctly evaluate their child's weight status. However, Pasch et al, 27 caution that attempts by pediatricians to correct parents' misperceptions about child weight may damage rapport and ultimately fail if the misperception is actually a reflection of parents' preferences, which may not be readily amenable to change.…”
Section: Resultsmentioning
confidence: 99%
“…9 Hasil yang hampir sama juga dilaporkan pada satu penelitian di Brasil dimana 45% orang tua menganggap anaknya memiliki status gizi normal meskipun pemeriksaan antropometri menunjukkan anak termasuk dalam gizi lebih (under estimation). 10 Selain itu juga dilaporkan bahwa usia, pekerjaan, pendidikan, status perkawinan dan penghasilan keluarga memengaruhi penilaian orang tua tentang status gizi anak. 11,12 Meskipun gangguan gizi pada anak telah banyak diteliti di Indonesia namun penelitian faktor-faktor yang memengaruhi kesalahan persepsi ibu tentang status gizi anak belum pernah dilakukan.…”
Section: Pendahuluanunclassified
“…Orang tua memilih jawaban dari tiga pilihan yaitu kurus, normal atau obesitas. 10,15 Penentuan status gizi ibu diukur berdasarkan BB dan TB yang dilaporkan oleh ibu melalui pengisian kuesioner (self-reported). Status gizi ibu diklasifikasikan berdasarkan IMT menurut kriteria Asia-Pasifik menjadi obesitas (kombinasi gemuk dan obesitas) dan bukan obesitas (kombinasi kurus, sangat kurus dan normal).…”
Section: Bahan Dan Metodeunclassified
See 1 more Smart Citation